2017
DOI: 10.2106/jbjs.15.01354
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the h-Index in Academic Orthopaedic Surgery

Abstract: Scholarly impact, as defined by academic productivity and scientific relevance, can be classified by the h-index and supplemented by the m and e-indices. This study has revealed well-defined differences in h, m, and e-indices with regard to academic rank among orthopaedic surgeons. Although the h, m, and e-indices may be of value as adjunct assessment devices for scholarly merit, careful consideration of their limitations must be maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
127
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 31 publications
10
127
1
3
Order By: Relevance
“…The h-indices of surgical oncologists appear to be higher across all academic ranks compared to neurosurgeons, otolaryngologists, plastic surgeons, radiation oncologists, and orthopedic surgeons. 68,12,14 This aligns with a previous report that faculty from the Division of Surgical Oncology were among the most academically productive within their Departments of Surgery, as measured by total publications, citations, and NIH funding. 3 Surgical oncologists’ higher h-indices likely reflect the presence of institutional research resources (within cancer centers), more readily available external funding including federal and foundational support, and perhaps the advent of genomic technologies and personalized oncotherapeutics.…”
Section: Discussionsupporting
confidence: 86%
“…The h-indices of surgical oncologists appear to be higher across all academic ranks compared to neurosurgeons, otolaryngologists, plastic surgeons, radiation oncologists, and orthopedic surgeons. 68,12,14 This aligns with a previous report that faculty from the Division of Surgical Oncology were among the most academically productive within their Departments of Surgery, as measured by total publications, citations, and NIH funding. 3 Surgical oncologists’ higher h-indices likely reflect the presence of institutional research resources (within cancer centers), more readily available external funding including federal and foundational support, and perhaps the advent of genomic technologies and personalized oncotherapeutics.…”
Section: Discussionsupporting
confidence: 86%
“…16 Furthermore, selfcitation can increase an author's h-index. 17,18 Despite these limitations, the h-index can be used as an indicator of both publication impact and academic advancement within orthopedic surgery. 17 The Journal of Hand Surgery authors had significantly higher mean total payments as reported in Open Payments compared with editors and reviewers.…”
Section: Discussionmentioning
confidence: 99%
“…First, we conducted a WoS-based analysis to understand the basic features of the publications in the sample, such as the H index; annual output; all authors, journals, institutions, and countries/regions of origin; and languages of publication. The H index and total number of citations reflect the quality and academic influence of publications at the institution or author level [16].…”
Section: Bibliometrics and Visual Analysismentioning
confidence: 99%